2010
DOI: 10.1007/s00264-010-1082-9
|View full text |Cite
|
Sign up to set email alerts
|

A computed tomography based study on rotational alignment accuracy of the femoral component in total knee arthroplasty using computer-assisted orthopaedic surgery

Abstract: Rotation of the femoral component in total knee arthroplasty (TKA) is of high importance in respect of the balancing of the knee and the patellofemoral joint. Though it is shown that computer assisted surgery (CAOS) improves the anteroposterior (AP) alignment in TKA, it is still unknown whether navigation helps in finding the accurate rotation or even improving rotation. Therefore the aim of our study was to evaluate the postoperative femoral component rotation on computed tomography (CT) with the intraoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…CT measurement depends on the technical ability of the work station to transcend points between serial axial cuts in order to assess tibial rotation. This technique is accurate and reproducible [4,11,12]. Intra-operative assessment of component rotation in primary knee arthroplasty relies on several landmarks.…”
Section: Discussionmentioning
confidence: 99%
“…CT measurement depends on the technical ability of the work station to transcend points between serial axial cuts in order to assess tibial rotation. This technique is accurate and reproducible [4,11,12]. Intra-operative assessment of component rotation in primary knee arthroplasty relies on several landmarks.…”
Section: Discussionmentioning
confidence: 99%
“…The use of computer-assisted surgery has also reduced the risk of malalignment associated with minimally invasive surgery (MIS) [5,6], which has potential issues with component malpositioning arising from the limited surgical view [7]. However, there were still errors in component alignment with computer-navigated TKA associated with the jig cutting setting, bone cutting and component implantation [8][9][10][11]. Navigation systems recommend checking for alignment of the bone cutting surface just after cutting the bone.…”
Section: Introductionmentioning
confidence: 99%
“…Axial alignment of the limb with restoration of the mechanical axis is a determinant of the outcome [2]. A number of studies [3][4][5] have suggested that alignment errors of >3°a re associated with more rapid failure and less satisfactory functional results.…”
Section: Introductionmentioning
confidence: 99%